1992
DOI: 10.1192/bjp.160.4.461
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia Following Pre-natal Exposure to Influenza Epidemics Between 1939 and 1960

Abstract: We examined the relationship between the dates of births of schizophrenic patients admitted to hospitals for the first time in England and Wales between 1970 and 1979, and the occurrence of influenza epidemics between 1939 and 1960. Our results indicate that exposure to influenza epidemics between the third and seventh month of gestation is associated with schizophrenia in adult life. The hypothesis that maternal viral infection is an important cause of schizophrenia can explain many aspects of the enigmatic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
1
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(110 citation statements)
references
References 20 publications
4
102
1
3
Order By: Relevance
“…43 There is also strong evidence suggesting that nonheritable factors in the pathogenesis of schizophrenia are associated with abnormalities during prenatal development. Indeed, epidemiological data show increased incidence of schizophrenia in humans prenatally exposed to virus, 44 gestational complications or malnutrition. 45,46 In addition, postmortem studies have indicated that certain limbic or associative brain areas of schizophrenic subjects have decreased cell numbers and volume, 47,48 disorganized cytoarchitecture, and reduced content of certain microtubule-associated proteins.…”
Section: Animal Modelsmentioning
confidence: 99%
“…43 There is also strong evidence suggesting that nonheritable factors in the pathogenesis of schizophrenia are associated with abnormalities during prenatal development. Indeed, epidemiological data show increased incidence of schizophrenia in humans prenatally exposed to virus, 44 gestational complications or malnutrition. 45,46 In addition, postmortem studies have indicated that certain limbic or associative brain areas of schizophrenic subjects have decreased cell numbers and volume, 47,48 disorganized cytoarchitecture, and reduced content of certain microtubule-associated proteins.…”
Section: Animal Modelsmentioning
confidence: 99%
“…13 Quarter of birth affects only a small fraction of all women's schooling decisions, however, and previous researchers have raised concerns about its exogeneity. Bound, Jaeger and Baker (1995), for example, cite several studies which suggest that quarter of birth is correlated with individual characteristics such as schizophrenia and autism (Sham et. al., 1992;Gillberg, 1990) or work experience since these may be affected by educational attainment.…”
Section: Assortative Mating Literaturementioning
confidence: 99%
“…A geneviral model of schizophrenia suggests that exposure to viruses initiates an immunological process that somehow disorganizes development of the fetal brain. 14,15 All three genes of the IL-1 gene complex (IL-1␣, IL-1␤, IL-1RA) are clustered on the long arm of human chromosome 2 in a region q13-q21. 16 The gene encoding IL-1RA has a variable number of tandem repeat polymorphisms in intron 2.…”
mentioning
confidence: 99%